Sintering condition-dependent electromechanical behavior of the lead-free piezoelectric Bi1/2K1/2TiO3 - Eyoum, Gina; Eckstein, Udo; Rieß, Kevin; Gadelmawla, Ahmed; Springer, Eva; Webber, Kyle Grant; Khansur, Neamul Hayet (Journal of Materials Science, 2022)
Sintering conditions govern the optimized functional properties of ceramics. However, solid-state processing of Bi1/2K1/2TiO3 (BKT), an important end member for lead-free piezoelectric solid solutions suitable for higher temperature (<= 300 degrees C) transducer applications, is challenging due to the low melting temperature (approximate to 1070 degrees C). In this work, the sintering temperature (1030 degrees C, 1050 degrees C, and 1060 degrees C) and dwell time (10 h, 20 h, and 40 h)-dependent functional properties of solid-state processed BKT were investigated, where the sintering condition-dependent dielectric and electromechanical properties were correlated with the variations in crystal structure and microstructure. Although X-ray diffraction data revealed a single-phase tetragonal structure of BKT at room temperature for all sintering conditions, significant changes in both the tetragonal distortion and spontaneous relaxor-ferroelectric transition were observed, which were directly related to the optimized functional properties. In addition, Rayleigh behavior of the piezoelectric coefficient was characterized between -150 degrees C and 400 degrees C, demonstrating that the electromechanical response is dominated by the intrinsic contribution, which can be explained by large tetragonal distortion and associated suppression of non-180 degrees domain wall motion.
CRIS-Team WoS Importer:2022-09-02